Promoting Academic Integrity in Virtual Classrooms: A Gamified Approach - Leithead, Cedar; Lin, Amy; Go, Naomi; Visutskie, Kasha; Foxe, John Paul; Miller, Allyson (Canadian Perspectives on Academic Integrity, 2023)
The sudden pivot to remote teaching in March 2020 highlighted new and emerging threats to academic integrity. While much of the world has returned to in-person delivery, in the classroom, remote teaching, and these associated threats to academic integrity, are here to stay. With the assistance of a Virtual Learning Strategy grant from eCampus Ontario, Seneca College and Toronto Metropolitan University have developed new gamified academic integrity modules for students designed to promote academic integrity in a virtual environment. The modules have been designed such that they apply to both college and university students and the code for the game is freely available under a Creative Commons License. In this presentation presenters will speak to how these modules were created as well provide a demonstration for all participants. By the end of this presentation attendees will be able to apply and adapt this resource to their own institution.